АНАЛІЗ КОНСТРУКТИВНИХ ОСОБЛИВОСТЕЙ З'ЄДНАНЬ СИЛОВИХ ЕЛЕМЕНТІВ КРИЛА ЛІТАКІВ ТРАНСПОРТНОЇ КАТЕГОРІЇ - Жиряков, Дмитрий Юрьевич (Open Information and Computer Integrated Technologies, 2020)
Ensuring the fatigue life of the aircraft structure is a requirement for flight safety, and for a cost-effective aircraft. A plane with a long lifetime can perform more flights, reduce routine maintenance costs and increase airline profits. Market trends in the aviation industry show the interest of airlines in long life aircraft. Structural elements of the wing are joined by fasteners. The wing structure fatigue is determined by the endurance of regular zones. Regular zones include longitudinal, transverse joints. The fatigue life of the wing irregular zones should be no less than the fatigue life of the regular zone. The article provides an analysis of the design features of the wing structural element joints performing short and medium flights, ANTONOV and Boeing, which have reached a high level in this field of research. Structural schemes of the wings, location and execution of the joints of the wing structural parts using facilities that improve take-off and landing characteristics (such as ailerons, flaps, slats and spoilers) are analyzed. The types, diameters and materials of fasteners that vary within the wing limits are considered. Attention was focused on such important indicators as the edge tolerance, distance between the fasteners (spacing), wing and fastener construction materials. The wing is made of a prefabricated structure, to ensure safety requirements for permissible destruction. In turn, this leads to an increase in the amount of fasteners. Since fatigue life is affected not only by the kinds of materials, parameters of fasteners, rated stresses, but also the degree of load transferring between parts. The constructive execution of the longitudinal and transverse connections of the load-bearing elements was analyzed to further study the degree of load transfer in a difficult - stressed state. The materials of the article provide an opportunity for further in-depth research on the general and local stress-strain state of the wing.